Pengaruh Ekstrak Daun Kemangi (Ocimum basilicum L.) Terhadap Pertumbuhan Streptococcus pneumoniae Secara In Vitro - Setiyani, Theresia; Furtuna, Dewi Klarita; ria, Fatma (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2023)
Streptococcus pneumoniae Â is the most common bacterium that causes community-acquired pneumonia. Basil leaves (Ocimum basilicum L.) have antibacterial compounds. The results of the phytochemical screening showed that basil leaves contain saponins, tannins and essential oils which have antibacterial activity. The purpose of this study was to prove the antibacterial effect of basil leaf extract (Ocimum basilicum L.) on the growth of Streptococcus pneumoniae . This study was conducted using the disc diffusion method, namely by soaking paper discs in basil leaf extract which had been prepared with concentration solutions of 25%, 50%, 75% and 100% for 15-30 minutes, then incubated at 37oC for 24 hours, then observed. clear zone formed. The results of this study were clear zones formed at each concentration of basil leaf extract. Basil leaf extract at concentrations of 25%, 50% and 75% can inhibit the growth of Streptococcus pneumoniae Â and the minimum inhibitory concentration is 25%. Keywords: Basil leaves (Ocimum basilicum L.), Antibacterial, Streptococcus pneumoniae